Determinan Konvergensi Pendapatan di Provinsi Sumatra Selatan - Nurhamidah, Rahma; Suhartini, Atik Mar'atis (Jurnal Ekonomi dan Pembangunan Indonesia, 2014)
Discrepancy of income between regions in South Sumatera province which tend to increase indicating high inequality. This study aims to analyze income convergence year 2006-2012 with sigma convergence and beta conditional convergence. The result with FD GMM show the existence income convergence and require 22 years to decrease half inequality by involving human capital and physic capital, that show slow process the convergence. Long road with small contribution to GDP per capita, causing slow income convergence. Hence, human capital and physic capital that existing especially long road should be optimized to accelerate income convergence between regions in South Sumatra province.